Clients’ satisfaction with continuity of midwifery care - Hanifatur Rosyidah; Noveri Aisyaroh (Poltekkes Kemenkes Yogyakarta, 2018)
The main problem in accelerating the decline in maternal mortality is not only the service coverage, but the quality of the service needs to be given special attention. One indicator is to know the quality of service that is the level of client satisfaction toward the service provided. The purpose of this research is to find out client satisfaction while getting assistance from midwifery students. Counseling begins in the second trimester of pregnancy until the birth and newborns for about 3 months. This study is a descriptive study, which describes or describes the facts or circumstances or visible symptoms. Samples in this study were 41 trimesters III pregnant women in the area of Puskesmas Bangetayu, Semarang. Overall, the respondents are satisfied with the assistance of midwifery students in midwifery care in Puskesmas Bangetayu, Semarang. This is evident from the high percentage of satisfaction and quality of service that equally shows very satisfied and good quality. There needs to be further research on the quality of service, particularly how the care provided or how the service progresses. Assistance is done from the beginning of the trimester of pregnancy or is done since pregnancy planning.